(3ehGgH GdQMef aj cTa YhQI GdTjWGfs - (3Ydj Hf ejehf Hf CHj HcQ Hf jhSa GdgGTej GdMSfj GdEOQjSj GdaGSj GdeZQHj, GHf ejehf , CHh GdMSf,J (B917 (3g` s ((3YHO GdhgGH Hf SdjeGf GdghT s)
(3ChdgG (B:s
(3GdMeO ddg ceG gh Cgdg CeG HYO habfG Gddg hEjGc deQVJGJg hGYde Cfc eJbdH heJQOO ai LejY CRefJc hChbGJc Hjf YOhjf eHjJjf faSc hYOh QHc GdQMef hYOhc hgh GdTjWGf GddYjf s
(3BNQgG (B:s
(3hdGMhd hdG bhI EdG HGddg GdYdi GdYXje hGZaQ dfG hdBHGFfG hdCegGJfG hdcGaI CfSGHfG Je HMeO Gddg hYhfg hMSf Jhajbg s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdMGOj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B27 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B251 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B741s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B2 - (3U (B1895s
Keywords: (3GdJUha hGdBOGH GdTQYjIs